Multisectoral approaches to nutrition - Garrett, James; Bassett, Lucy; Levinson, F. James (International Food Policy Research Institute, 2011)
Multisectoral thinking has long been attractive in the field of development, especially in the social sector, because social problems and their determinants are so complex and multifaceted. For nutrition, UNICEF's (1990) conceptual framework of the causality of child malnutrition illustrates the multisectoral nature of the problem (Figure 2.1). It shows the immediate determinants of malnutrition at the individual level (inadequate dietary intake and disease) as products of underlying causes at the family or household level (insufficient access to food, inadequate maternal and child practices, poor water and sanitation, and inadequate access to quality health services). These, in turn, are influenced by basic causes at a societal level, including the quality and quantity of human, economic, and organizational resources and the way (or by whom) they are controlled. More fundamentally, these factors operate within a given—although dynamic—economic, political, cultural, and social structure, where each actor has specific resources.